Molasses-Based Block Supplements for Cattle Fed Endophyte-Infected Tall Fescue (Festuca arundinacea) Seed: Effects on Growth Performance, Circulating Biomarkers, Heat Stress, and Coccygeal Artery Diameter - Luis F. B. B. Feitoza; Brad J. White; James S. Drouillard (Animals)
Ergot alkaloids present in endophyte-infected tall fescue can cause a series of negative effects in exposed cattle. This study evaluated the effectiveness of molasses-based block supplements (MBSs) in alleviating vasoconstriction, which leads to reduced peripheral blood flow, heat stress, and impaired growth performance in cattle. A total of 100 crossbred steers were assigned to five treatment groups: a negative control with no tall fescue seed; a positive control with ergot-infected tall fescue seeds; and three MBS treatments, including a control block, a block containing menthol, and a block containing capsaicin. Blood flow was assessed through ultrasound imaging of the coccygeal artery, while thermal imaging was used to monitor body temperature regulation. Growth performance, feed intake, and blood biomarkers were also measured. Cattle consuming MBS had improved weight gain, greater arterial diameters, and enhanced thermoregulation compared to those without supplements. No significant differences were observed between the different MBS formulations. These results suggest that molasses-based block supplementation can help mitigate heat stress and poor growth performance associated with ergot alkaloid consumption, potentially providing a practical nutritional strategy for cattle producers managing cattle exposed to ergot alkaloids.